Coinfection and Genetic Characterization of Porcine Astrovirus in Diarrheic Piglets in China From 2015 to 2018 - Su, Mingjun; Qi, Shanshan; Yang, Dan; Guo, Donghua; Yin, Baishuang; Sun, Dongbo (Frontiers in Veterinary Science, 2020)
Porcine astrovirus (PAstV) is broadly distributed globally and existing as at least five distinct genotypes. Recently, PAstV has been reported as an important pathogen of diarrhea in piglets, and widely distributed in China. However, there are few studies on the co-infection and genetic characterization of PAstV in diarrheic piglets in China. In this study, 89 PAstV-positive samples were collected from 543 diarrhea samples in China during 2015-2018. Of these 89 PAstV-positive diarrhea samples, 77.53% (69/89) of samples were co-infected with four to six different porcine pathogens, and none of samples were positive for PAstV only. Among the 543 diarrhea samples, a statistical analysis showed that PAstV-induced diarrhea was potentially associated with co-infection of PEV (p<0.01) and GARV (p<0.01). Phylogenetic analysis showed that the 27 identified PAstV strains belong to three different genotypes, that the PAstV-2 (81.48%, 22/27) was predominant in diarrheic piglets in China, followed by PAstV-4 (11.11%, 3/27) and PAasV-5 (7.41%, 2/27). Sequence analysis revealed that the 27 RdRp genes identified in this study exhibited nucleotide homologies of 53.8%-99.5%. In addition, RdRp gene of the PAstV-4 strain JL/MHK/2018/0115 harbored a unique insert of three nucleotides (GAA) when compared with other known PAstV-4 strains. Genotype distribution showed the genotypes of PAstV varies with the different geographical location, and PAstV-2 was the most widely distributed in China. These data demonstrated that PAstV co-infection with other porcine pathogens was common and genetic diversity of PAstV was existed in diarrhea-affected piglets in China.